Immuno-oncology therapy in metastatic bladder cancer: A systematic review and network meta-analysis. (January 2022) - Chierigo, Francesco; Wenzel, Mike; Würnschimmel, Christoph; Flammia, Rocco Simone; Horlemann, Benedikt; Tian, Zhe; Saad, Fred; Chun, Felix K.H.; Tilki, Derya; Shariat, Shahrokh F.; Gallucci, Michele; Borghesi, Marco; et al.
Graphical abstract: Highlights: NMA comparing available IO-based regimens in 1 st or 2 nd line therapy for advanced or metastatic bladder cancer has never been conducted In 1 st line setting, compared with CT, no IO-based regimen exhibited survival benefit. In 2 nd line setting, compared with CT, only pembrolizumab improved OS benefit. All exclusive IO regimens resulted in lower rates of grade 3+ AEs both in first- and second-line settings. Abstract: Context: Three first line and three second-line clinical trials tested the effect of immunotherapy (IO) relative to standard chemotherapy (CT) on overall survival. However, network meta-analysis-based comparisons have not yet been presented. We addressed this void. Objective: To provide comparisons of overall survival (OS), progression-free survival (PFS), complete response (CR), partial response (PR), stable disease (SD), objective response rates (ORR), disease control rates (DCR) and adverse events (AEs) associated with 1st and 2nd line IO-based regimens. Materials and methods: PubMed was searched for phase III randomized controlled trials from 2016 to 2021, including conference abstracts. We identified three first line [IMvigor130 (atezolizumab + CT vs atezolizumab vs CT), DANUBE (durvalumab vs durvalumab + tremelimumab vs CT), and KEYNOTE-361 (pembrolizumab + CT vs pembrolizumab vs CT)] and two second line [KEYNOTE-045 (pembrolizumab vs CT) and IMvigor211 (atezolizumab vs CT)] RCTs. Results: Overall, 3255 and 1452 patients were respectively included in the first- and second-line settings. In 1st line setting, compared with CT, no IO-based regimen exhibited survival benefit. However, all exclusive IO regimens resulted in lower rates of grade 3+ AEs. In 2nd line setting, compared with CT, only pembrolizumab improved OS benefit. Conversely, atezolizumab only showed OS benefit in exploratory analyses. Compared to second-line CT, no experimental regimen (atezolizumab or pembrolizumab) exhibited statistically significant ORR benefit. Both pembrolizumab and atezolizumab resulted in lower rates of grade 3+ AEs compared to 2nd line CT. Conclusions: In metastatic UC, IO-based regimens do not hold a survival benefit relative to CT in 1st line setting. However, pembrolizumab holds a survival benefit in 2nd line compared to CT. Several IO-based clinical trials are ongoing and will provide more and possibly better treatment alternatives for locally advanced and metastatic UC.